Genetic diagnosis of workers: recent scientific findings, ethical and ethical-legal problems - Mele, Vincenza; Girlando, Giuseppina; Sgreccia, Elio (Medicina e Morale, 1990)
This article suggests some ethical guidelines for the genetic diagnosis of workers in the light of personalistic ethical principles, and takes into account the contribution of the most important European and American legal documents. The ethical and legal consideration is founded on the recent scientific discoveries about the association between genetic status and professional diseases and the article discusses many factors like the certainty of such an association, the seriousness of the disease and the aims of the diagnostic test.